Effect of laser on erythrocytes sedimentation rate and some hematological parameters - Shaker, Eman A.; Rasheed, Nabaa A; Salman, Zainab R. (Journal of the Faculty of Medicine Baghdad, 2017)
Background: This study was conducted in pursuit of gaining an understand effects of the low level laser irradiation on whole blood is very essential way in revealing the mechanisms of the action of laser radiation  on biological tissues.Objective: The purpose of this study is to investigate the in vitroeffect of laser radiation on some hematological parameters and erythrocyte sedimentation rate.Subject and Method: Blood samples were obtained from 30 healthy volunteers, each sample was divided  into four new samples, one of them was considered as control while the other three were exposed to three  different laser doses. Thewavelength of532nm was used for irradiation with 4mm diameter beam spot on blood samples, with power density of 796.17mW/cm2. The irradiation times were 1.8, 3.7and 6.2 secand so  the different doses of irradiation 1.5,3 and 5 J/cm2, respectively.Results: The erythrocyte sedimentation rate was measured after laser irradiation and compared with un-irradiated control sample. The results of this study showed thaterythrocyte sedimentation rate value increased significantly with a dose of 1.5J/cm² but not with the othertwo doses’ values in male persons but not in females. Moreover, the mean cell volume shows significant decrement post irradiation.Conclusion: Laser irradiation induces physical changes in red blood cell membrane permeability and blood viscosity and consequently alters erythrocyte sedimentation rate.